2008
DOI: 10.1590/s1413-35552008000200012
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades psicométricas da versão brasileira da escala de qualidade de vida específica para acidente vascular encefálico: aplicação do modelo Rasch

Abstract: Background: Stroke results in important defi cits, which reduce individuals' quality of life (QOL). Specifi c QOL measurements are necessary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 26 publications
(40 reference statements)
1
29
0
24
Order By: Relevance
“…Considering participant characteristics, the profile was similar to that of other investigations conducted in Brazil [21][22][23] , in which the occurrence of stroke was more frequent among individuals over 60 years of age 21,22 and with a slight predominance of women 23 . According to Cavalcante et al 23 , the predominance of women affected by stroke may have been related Cronbach's α SF-36 0.79 to age, because nationally women live longer than men.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Considering participant characteristics, the profile was similar to that of other investigations conducted in Brazil [21][22][23] , in which the occurrence of stroke was more frequent among individuals over 60 years of age 21,22 and with a slight predominance of women 23 . According to Cavalcante et al 23 , the predominance of women affected by stroke may have been related Cronbach's α SF-36 0.79 to age, because nationally women live longer than men.…”
Section: Discussionsupporting
confidence: 79%
“…According to Lima et al 21 , generic instruments may underestimate the impact of stroke, since they are less sensitive to the effects of specific health conditions. Therefore, there is not a single instrument capable of assessing all health situations and the choice of an instrument should be associated with the objectives of the study, language accessibility, and cultural context 9 .…”
Section: Discussionmentioning
confidence: 99%
“…(8) The SS-QOL is a specific instrument to assess health-related quality of life among people who suffered a stroke, which was culturally validated and adapted to Brazil. (9,10) It lists 49 items in 12 domains and its scoring goes from 49 to 245 points. Answers vary from 1 to 5 points; higher figures indicate better health-related quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…The adaptation of the Brazilian version of Stroke-Specific Quality of Life (SS-QOL), translated as Escala de Qualidade de Vida Específica para Acidente Vascular Encefálico (EQVE-AVE), was used as a specific measure of the quality of life 21 . The measurement properties of the Brazilian version of the SS-QOL were assessed by Lima et al 21 , who concluded that the instrument was adequate and clinically useful for the population evaluated.…”
Section: Stroke-specific Quality Of Life (Ss-qol)mentioning
confidence: 99%
“…The measurement properties of the Brazilian version of the SS-QOL were assessed by Lima et al 21 , who concluded that the instrument was adequate and clinically useful for the population evaluated.…”
Section: Stroke-specific Quality Of Life (Ss-qol)mentioning
confidence: 99%